Державна політика антикризового розвитку реального сектору економіки України: автореф. дис… на здобуття наукового ступеня доктора наук з державного управління - Ортіна, Ганна Володимирівна; Ortina, Hanna (Харків : Національний університет цивільного захисту України, 2017)
UA: Дисертацію присвячено обґрунтуванню теоретико-методологічних положень формування та реалізації державної політики антикризового розвитку реального сектору економіки України. У роботі досліджено ґенезу причин виникнення криз в глобалізованій ринковій економічній системі. Уточнено сутність державної політики антикризового розвитку реального сектору економіки. Виявлено плив тенденцій глобалізації на умови формування та реалізації державної політики антикризового розвитку національної економіки. Удосконалено методологічні положення формування та реалізації державної політики антикризового розвитку реального сектору економіки. Здійснено аналіз розвитку реального сектора економіки України та напрямів формування державної антикризової політики. Розроблено наукову концепцію державної політики антикризового розвитку реального сектору економіки. Запропоновано модель-схему модернізації реального сектора економіки в рамках державної політики антикризового розвитку. На основі економіко-математичного моделювання обґрунтовано науково-методологічний підхід до розподілу бюджетних коштів на реалізацію модернізації реального сектора економіки в рамках державної політики антикризового розвитку. Розроблено механізми реалізації державної політики антикризового розвитку реального сектора економіки в умовах глобалізації. EN: The dissertation is devoted to the substantiation of theoretical and methodological provisions of the formation and implementation of the state policy of crisis management of the real sector of the Ukrainian economy. The paper examines the genesis of the causes of crises in the globalized market economy system. The essence of the state policy of anti-crisis development of the real sector of the economy is specified. The emergence of globalization tendencies on the conditions for the formation and implementation of the state policy of the crisis-based development of the national economy was revealed. The methodological provisions of the formation and implementation of the state policy of crisis management of the real sector of the economy have been improved. The analysis of the development of the real sector of the economy of Ukraine and the directions of the formation of the state anti-crisis policy was carried out. The scientific concept of the state policy of crisis development of the real sector of the economy has been developed. The model scheme of modernization of the real sector of the economy within the framework of the state policy of anti-crisis development is proposed. On the basis of economic mathematical modeling, the scientific and methodological approach to allocating budget funds for realization of modernization of the real sector of the economy in the framework of the state policy of crisis-based development was substantiated. Mechanisms for realization of the state policy of crisis-based development of the real sector of economy in the conditions of globalization are developed.
State policy of anti-crisis development of the real sector of the economy of Ukraine
Keywords: антикризовий розвиток; державна політика; державне управління; механізм державного управління; реальний сектор економіки; anti-crisis development; state policy; public administration; mechanism of public administration; real sector of economy